PREVALENCE AND PREDICTORS OF DIABETES AMONG ADULTS IN RURAL DHARWAD, INDIA: A CROSS-SECTIONAL STUDY - Tamboli, Shrinivas Sangappa; B, Ramamurthy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Diabetes is a long life chronic non-communicable disease and emerging fast as one of the most serious health problems in developed and developing countries, also influences the risk of developing macrovascular complication including heart disease and stroke which are the leading causes of global death. This study aims to find the potential risk factors associated to diabetes among different community (Government, Private employees, and Businessmen) of adults 20 years and above. Methods: A cross-sectional study followed and conducted door-to-door survey using World Health Organization STEP Surveillance (WHO STEPS) questionnaire to collect the information of sociodemographic, anthropometric and behavioral characteristics. Multiple logistic regression is used to determine the risk factors of diabetes among study population. Data was pre-processed and used Chi-square test and t-test to find the comparison between the attributes. Results: Overall prevalence of diabetes is found to be 49.1% in which prevalence more in females with 51.7% than in males with 46.8%, the education, health examination, and waist circumference were found to be the potential risk factors. The total study subjects include 1083 in which male is 611 and female is 472. Conclusion: The current study reflects the importance of Diabetes disease among the study population in rural Dharwad and this study can be utilized to control and prevent diabetes. It’s an early call for the females of the study population to take care and practice healthy food in day today life and the outcome of the study says that the education should be given prime importance in everyone’s life.